Clinical evidence supporting ceftaroline fosamil and ceftobiprole for complicated skin and soft tissue infections. Issue 2 (13th April 2023) - Leventogiannis, Konstantinos; Mouktaroudi, Maria; Giamarellos-Bourboulis, Evangelos J.
Abstract : Purpose of review: Ceftaroline and ceftobiprole are advanced generation cephalosporins with activity against methicillin-resistant Staphylococcus aureus (MRSA). This review summarizes their clinical efficacy for complicated skin and soft tissue infections (cSSTIs). Recent findings: Both these agents retain excellent in vitro activity against both MRSA and Gram-negative isolates from patients with CSSTIs. Both these agents are registered for the management of cSSTIs based on the results of large scale phase III noninferiority trials. Ceftaroline and ceftobiprole are noninferior to the combination of vancomycin and aztreonam as this was assessed by their clinical cure rate at the test-of-cure visits. Furthermore, ceftobiprole is noninferior to comparators for the achievement of early clinical success at 72 h. Ceftaroline achieves 81% clinical cure against diabetic foot infections. Summary: Ceftaroline and ceftobiprole can be used as monotherapy for the treatment of cSSTIs.